Actors Distortion of News Agencies Framing Surveys in Online Mass Media about Political Parties Bearer Presidential-Candidates 2024 - Dwinarko Dwinarko; Tabrani Sjafrizal; Pagi Muhamad; Moh. Rivaldi Akbar (Syntax Corporation Indonesia, 2023)
This research aims to acknowledge the News Framing of political actors in online mass media in determining presidential candidates in 2024. A political actor is an individual who plays a role in networking and Communication actions, acting as individuals, groups, or organizations. Political actors in the black box in the theory of actor networks are framed through the processing of information resulting from the social interactions of individual actors involved in everyday life, who are tied to systems and ideologies regarding their views on a political party reality. The actions of actors Survey institutions and online mass media in the community model network of actors with a situational approach. The theory used is the theory of actor networks and qualitative descriptive research methods with a narrative approach to analyzing online mass media news framing. The study’s result shows an integrated black box between the theory of actor networks and the theory of communicative actions. The news framing indicates a distortion of survey agency actors through online mass communication networks due to the efforts of survey agency actors. Unreliable survey results deceive political party actors in the presidential nomination of the Republic of Indonesia in 2024 who cannot carry actors in political parties. Political Parties are distorted due to the lack of use of internal survey agencies of political parties and the role of Political Parties Actors, which is still minimal to socialize with constituents, as well as dependence on external survey agencies, which are profit organizations. Political Parties are incapable of producing leaders who are already institutionally managed. Further research recommendations on the role of Political Parties actors in managing quality Human Resources in collecting and preparing actors ready to become national leaders.